2017
DOI: 10.1155/2017/6307019
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Variation in Morphometry of Human Coracoid Process among Asian Population

Abstract: Ethnic origin plays an important role in bone morphometry. Studies examining the influence of coracoid process have focused primarily on adults and have not included people from diverse Asian ethnic backgrounds. Our goal was to explore ethnic differences in morphometry of coracoid among Asian population. We performed morphometric measurements of coracoid process on cadaveric shoulders and shoulder CT scans from 118 specimens. The cadaveric sample included Indian (46%), Chinese (27%), and Myanmarese (27%) subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
4
17
3
Order By: Relevance
“…The coracoid morphological parameters stratified by gender showed that all parameters were significantly greater in males than in females, which is in agreement with the findings of previous studies [24,29,31,33,38]. Conversely, Imma et al [27] found significant sexrelated differences in the measurements except for the base height, tip length, and midpoint width.…”
Section: Gender Differences In Morphometric Measurements Of the Coracsupporting
confidence: 91%
“…The coracoid morphological parameters stratified by gender showed that all parameters were significantly greater in males than in females, which is in agreement with the findings of previous studies [24,29,31,33,38]. Conversely, Imma et al [27] found significant sexrelated differences in the measurements except for the base height, tip length, and midpoint width.…”
Section: Gender Differences In Morphometric Measurements Of the Coracsupporting
confidence: 91%
“…It is evident that the dimensions of the coracoid process in the present study show similarities with the earlier studies. However, the values of the thickness of coracoid process recorded in the present study are at appreciable variance with the result of the study done by Fathi et al (9).…”
Section: Discussioncontrasting
confidence: 51%
“…Therefore, in 46% of the cases there was less than the ideal length of 25 mm, according to the original technique [11,15] [19,20]. From the aforementioned studies and the international literature, the coracoid length seems to be positively affected by male gender, age, overall height and Caucasian genetics [12,13,17,20,21]. In our study population, the height of the cadavers was not available, however we observed a positive correlation with the glenoid height.…”
Section: Discussionmentioning
confidence: 60%